2013
DOI: 10.1111/eci.12106
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, visfatin and regional fat depots in normal weight obese premenopausal women

Abstract: Compared with healthy controls, women with NWO had higher DBP, TG, LDL, and regional fat and lower HDL. These findings seem to be associated more with excess Android fat than excess %BF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Compared with the gynoid pattern, the android pattern of fat distribution is considered to be more metabolically active and has been associated with increased risk of cardiovascular disease [ 19 , 20 ], abnormal lipid profiles and diastolic blood pressure [ 21 ]. It is also becoming increasingly recognized that the android pattern of fat distribution is an important determinant of the burden of musculoskeletal diseases and a recent study has shown that android fat is strongly associated with foot pain and disability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the gynoid pattern, the android pattern of fat distribution is considered to be more metabolically active and has been associated with increased risk of cardiovascular disease [ 19 , 20 ], abnormal lipid profiles and diastolic blood pressure [ 21 ]. It is also becoming increasingly recognized that the android pattern of fat distribution is an important determinant of the burden of musculoskeletal diseases and a recent study has shown that android fat is strongly associated with foot pain and disability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some, a lack of association was found [13,20,23], while in others visfatin/NAMPT level was proportional [19][20][21][22][23][24][25] or even inversely related [22,26] to insulin resistance. It has been suggested that the described differences could be explained by a varied intensity of inflammation, related more to activation of monocytes circulation compared to macrophages in adipose tissue [27].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, previous data has shown similar findings for trunk fat, with NWO females demonstrating higher levels. WHR data is mixed with some reporting higher ratios in NWO, [38][39][40] with others showing no difference 103,109 . The diverse outcomes displayed in this study compared to previous literature are not entirely unexpected.…”
Section: Body Compositionmentioning
confidence: 97%